Self-Efficacy of Workshop Class Students in Learning the Qur'an Ummi Method - Zulva Rojauna; Asriana Kibtiyah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This qualitative descriptive study examines the self-efficacy of underachieving students in workshop classes learning the Quran through the Ummi method at Madrasah Tsanawiyah Al Washoya Kertorejo Ngoro Jombang. Nine workshop class students who failed to achieve the munaqosyah targets within one year were selected as subjects. Data collection employed in-depth interviews, direct classroom observations, documentation analysis, and Likert scale questionnaires. Self-efficacy was analyzed through five indicators: choice behavior, effort expenditure, persistence, thought patterns, and emotional reactions, derived from Bandura's cognitive, motivational, affective, and selection processes. Results indicate that workshop class students demonstrate low self-efficacy levels across most indicators. Choice behavior reveals poor time management with a preference for non-productive activities. Effort expenditure and persistence show high dependence on extrinsic motivation from teachers rather than intrinsic drive. However, thought patterns exhibit positive tendencies, with students expressing aspirations to practice and teach Quranic knowledge. Emotional reactions predominantly reflect boredom and lack of enthusiasm due to repetitive materials and frequent instructor changes. The Ummi method implementation through the halaqah system with seven systematic stages proves effective in creating conducive learning environments. However, improving self-efficacy requires additional interventions, including intensive mentoring, instructor stability, and supportive learning environments. These findings reinforce Bandura's reciprocal determinism theory and contribute to understanding self-efficacy dynamics in religious education contexts